Clinical motivation and the surgical safety checklist. Issue 4 (3rd February 2017) - Yu, X; Huang, Y; Guo, Q; Wang, Y; Ma, H; Zhao, Y; Wang, Y; Yu, X; Tan, G; Ma, S; Wu, X; Xu, M; et al.
Abstract: Background: Although the surgical safety checklist (SSC) has been adopted worldwide, its efficacy can be diminished by poor clinical motivation. Systematic methods for improving implementation are lacking. Methods: A multicentre prospective study was conducted in 2015 in four academic/teaching hospitals to investigate changes during revision of the SSC for content, staffing and workflow. All modifications were based on feedback from medical staff. Questionnaires were used to monitor dynamic changes in surgeons', nurses' and anaesthetists' perceptions. Results: Complete information was obtained from 30 654 operations in which the newly developed SSC system was used. Implementation quality was evaluated in 1852 operations before, and 1822 after the changes. The revised SSC content was simplified from 34 to 22 items. Anaesthetists achieved widespread recommendation as SSC coordinators. Completion rates of all stages reached over 80·0 per cent at all sites (compared with 10·2–59·5 per cent at the sign-out stage in the baseline survey). There was a significant change in doctors who participated (for example, surgeon: from 24·6 to 64·5 per cent at one site). The rates of hasty (15·1–33·7 per cent) or casual (0·4–4·4 per cent) checking decreased to less than 6·0 per cent overall. Perceptions about the SSC were studied from 2211 forms. They improved, with a converging trend among the three different professions, to a uniform 80·0 per cent agreeing on the need for its regular use. Conclusion: Medical staff members are both the users and owners of the SSC. High-quality SSC implementation can be achieved by clinically motivated adaptation. Abstract : Buy-in issues similar worldwide